AGAINST RISK-BENEFIT REVIEW OF PRISONER RESEARCH - Chwang, Eric (Bioethics, 2010)
The 2006 Institute of Medicine (IOM) report, ‘Ethical Considerations for Research Involving Prisoners’, recommended five main changes to current US Common Rule regulations on prisoner research. Their third recommendation was to shift from a category-based to a risk-benefit approach to research review, similar to current guidelines on pediatric research. However, prisoners are not children, so risk-benefit constraints on prisoner research must be justified in a different way from those on pediatric research. In this paper I argue that additional risk-benefit constraints on prisoner research are unnecessary: the current Common Rule regulations, omitting category-based restrictions but conjoined with the IOM report's other four main recommendations, ensure that prisoner research is as ethical as non-prisoner research is. I explain why four problems which which may be more prevalent in prisons and which risk-benefit constraints may seem to address – coercion, undue inducements, exploitation, and protection from harm – are in fact not solved by adding further risk-benefit constraints on prisoner research.